2023
DOI: 10.3389/fnins.2023.1119405
|View full text |Cite
|
Sign up to set email alerts
|

High vagally mediated resting-state heart rate variability is associated with superior working memory function

Abstract: BackgroundHeart rate variability (HRV), a cardiac vagal tone indicator, has been proven to predict performance on some cognitive tasks that rely on the prefrontal cortex. However, the relationship between vagal tone and working memory remains understudied. This study explores the link between vagal tone and working memory function, combined with behavioral tasks and functional near-infrared spectroscopy (fNIRS).MethodsA total of 42 undergraduate students were tested for 5-min resting-state HRV to obtain the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…These studies illustrate that trait vmHRV is positively associated with cognitive outcomes. A recent study by Zeng et al (2023) has further substantiated these findings by demonstrating that increased performance of individuals with high resting-state vmHRV on a WM task was related to higher efficiency in regulating neural resources in the prefrontal cortex, as compared with their lower vmHRV peers. From a resource -dependent perspective, vmHRV reactivity during task performance and vmHRV rebound during a post-task recovery period are indices used to represent prefrontal resource consumption.…”
Section: Introductionmentioning
confidence: 84%
“…These studies illustrate that trait vmHRV is positively associated with cognitive outcomes. A recent study by Zeng et al (2023) has further substantiated these findings by demonstrating that increased performance of individuals with high resting-state vmHRV on a WM task was related to higher efficiency in regulating neural resources in the prefrontal cortex, as compared with their lower vmHRV peers. From a resource -dependent perspective, vmHRV reactivity during task performance and vmHRV rebound during a post-task recovery period are indices used to represent prefrontal resource consumption.…”
Section: Introductionmentioning
confidence: 84%
“…The negative correlation between HF and ranking score suggests that players with higher ranks and, therefore, higher levels of expertise in LOL, have relatively lower in-game parasympathetic activity. Previous studies have demonstrated that subjects with high vagally-mediated HRV/parasympathetic tone at rest often have superior behavioral performance in cognitive tasks assessing working memory and executive control (Magnon et al, 2022;Zeng et al, 2023) as well as in real-world tasks such as chess playing (Beffara et al, 2016;Fuentes-Garcia et al, 2019b). Top players in LOL are known to have better impulsive/interference control and cognitive exibility relative to average players (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Результати низки метааналізів свідчать, що функціональний стан ВРС у пацієнтів із ПТСР пригнічений [75,88]. RMSSD, HF-компонент спектра ВРС і парасимпатична (вагусна) активність взаємопов'язані [89]. Метааналіз із використанням моделі випадкових ефектів продемонстрував, що у хворих із ПТСР спостерігається значно вища ЧСС, а також показники співвідношення середніх значень низькочастотної (LF) та HF-компоненти (LF/HF) спектру ВРС.…”
Section: посттравматичний стресовий розлад вегетативна нервова систем...unclassified